Analisis problematika penggunaan bahasa Indonesia pada karangan narasi peserta didik kelas IV Sekolah Dasar - Ahyaitasyarafa, Afina; Slamet, Slamet; Surya, Anesa (Universitas Sebelas Maret, 2022)
The purpose of this study was to identify and describe the problematic forms of using Indonesian in narrative essays for fourth grade students at SDN Tegalayu Surakarta. The problems studied include (1) problematic language symptoms, (2) spelling and usage problems, (3) word form and meaning changes, (4) sentence problems. This research is a qualitative research with a case study approach. The sampling technique used was representative research subjects, namely fourth grade students at SDN Tegalayu Surakarta. The data analyzed is a narrative essay of students. Data collection techniques using document analysis, interviews, and observations. Test the validity of the data using technical triangulation and source triangulation and refers to the KBBI and PUEBI. The data analysis technique used interactive analysis techniques. The most problems were spelling and usage problems of 36.16%, followed by problems of changing word forms and meanings 35.03%, sentence problems 15.25% and language symptoms problems of 13.56%. The main causes of problems are (1) lack of understanding of students' linguistic rules, (2) lack of mastery of students' vocabulary, (3) low motivation and interest of students, (4) student accuracy. So that teachers need to plan learning strategies that can reduce the problems of using Indonesian in students.